The Role Of Women In Actualizing Themselves In The Life Of The Medan City Community - Aisyah, Nur (Journal Research of Social Science, Economics, and Management, 2023)
North Sumatra has a population of 14.8 million people, and Medan municipality has 2.4 million people, consisting of 1.21 million men and 1.22 million women. Women are more than men, with the assumption that self-actualization is more shown by women. The purpose of this study is how the role of women in self-actualizing in the life of the Medan city community. This research uses data collection methods through qualitative methods of case study interviews through informants. The subjects of this research are 4 women who are members of the IWAPI Organization, FKMI. The results showed that women's self-actualization is the potential of a person, especially women, to be realized and maximize their potential, in this case the women in the IWAPI Organization, FKMI and have chosen and determined the choice of organization as a suitable forum and are able to position themselves as self-actualizing women. The self-actualization of women in IWAPI, FKMI and these organizations is not at all hampered by the existence of government regulations or government policies that are discriminatory. Based on observations and documentation data from women researchers in the IWAPI Organization, FKMI that along with the impact of the COVID-19 pandemic, encourages self-improvement through self-actualization in the family and community life of Medan city.